Influence of single-fraction Gamma-Knife radiosurgery on ocular surface and tear function in choroidal melanoma patients. Issue 4 (24th January 2013) - Horwath-Winter, Jutta; Schneider, Mona Regina; Wackernagel, Werner; Rabensteiner, Dieter; Boldin, Ingrid; Haller-Schober, Eva-Maria; Langmann, Gerald
Abstract : Aim: To evaluate ocular surface and tear function in patients with choroidal melanoma treated with single-fraction radiosurgery. Methods: 36 patients (median age 62 years; range 26–84 years) were enrolled between 2001 and 2006 at a single institution. They were treated with the Leksell Gamma Knife in one fraction with a median dose of 30 Gy (range 25–35 Gy). In both eyes of all patients treated subjective symptom score (visual analogue scale) was evaluated, central corneal sensitivity testing, Schirmer test without local anaesthesia, and corneal and conjunctival staining were performed before therapy and 3, 6, 12, 24 and 36 months thereafter. The respective untreated fellow eye served as control. Results: Three months after radiosurgery, the subjective dry eye symptom score and lissamine green staining score of the ocular surface were significantly higher in the treated eyes compared with the fellow eyes (p<0.001, p=0.028, respectively). After 12 months, a significant difference between the treated and the fellow eyes in corneal sensitivity (p=0.041) and corneal fluorescein staining (p=0.002) was found when compared with pretreatment values. After 24 months Schirmer test values without local anaesthesia were significantly reduced in the treated eyes vis-à-vis untreated fellow eyes and pretreatment values (p=0.004). The dose applied to the lacrimal gland was significantly correlated to ocular surface staining scores (p=0.001) and Schirmer test values (p=0.026) at 24 months after irradiation. Conclusions: Stereotactic single-fraction Gamma-Knife radiotherapy of choroidal melanoma with a median dose of 30 Gy significantly affected ocular surface and tear function and increased dry eye symptoms and signs.